دور الوسائل التعليمية في تنمية مهارة فهم المنطوق و انتاجه لدى تلاميذ السنة الخامسة ابتدائي - عروة, رحومة, هندة مروة (University of El-oued, 2021)
من خلال ما سبق عرضه في الفصل السابق تلخص إلى القول أن الوسائل التعليمية الحديث تحتل مكانة مرموقة بين المدخلات التربوية لتعدد فوائدها، وتحظى بأهمية بالغة لدى المعلمين، حيث أنها تؤدي إلى استشارة اهتمام المتعلم واشباع تقدم خبرات متنوعة يأخذ ، فلا شك أن الوسائل التعليمية "الحديثة " خاصة منها الحاسب الآلي والإنترنت ،حاجاته للتعلم فهي تساعد المعلم إلى حد كبير في أداء عمله في جميع مجالات التدريس وهذا ما سنتطرق ،منها كل متعلم ما يحقق أهدافه إليه في الفصل الثاني. و كخلاصة لهذا الفصل نستنتج أن نشاط فهم المنطوق أضفى الكثير على ميدان التعليم، فهو بدو ره يهدف إلى صقل حاسة السمع وتنمية مهارة الاستماع، كما يعمل على توظيف اللغة من خلال الإجابة عن أسئلة متعلقة بنص مما يكتسب التلميذ الكثير من المفردات، ويجعله يتعلم أنماط الجمل والتراكيب متلقيا الَفكار والمفاهيم ويستطيع بفضله أن يكتسب المهارات الَخرى للغة كلاما وقراءة و كتابة، فالاستماع الجيد شرط أساسي لحماية التلميذ من الوقوع في أخطاء كثيرة، والقدرة على التحدث ويتبعها القدرة على القراءة والكتابة. الكلمات Through what was previously presented in the previous chapter, it was summarized to say that modern educational means occupy a prominent position among educational inputs due to the multiplicity of their benefits, and are of great importance to teachers, as they lead to consulting the learner’s interest and satisfying his learning needs. There is no doubt that “modern” educational means are especially Including computers and the Internet, they provide a variety of experiences from which each learner takes what achieves his goals. It helps the teacher to a large extent in performing his work in all areas of teaching, and this is what we will discuss in the second chapter. The activity of verbal comprehension has added a lot to the field of education. It in turn aims to refine the sense of hearing and develop the listening skill. It also works on the use of language by answering questions related to a text, which makes the student acquire a lot of vocabulary, and makes him learn patterns of sentences and structures, receiving ideas and concepts, and thanks to him he can Acquires other language skills in speech, reading and writing. Good listening is a prerequisite for protecting the student from making many mistakes, and the ability to speak, followed by the
Keywords: الوسائل التعليمية، فم المنطوق، التعبير الشفوي، الاستماع; teaching aids, oral expression, oral expression, listening